Migration and Regional Convergence in the European Union - Peter Huber; Gabriele Tondl (Austrian Institute of Economic Research (WIFO), 2012)
We offer an empirical, econometric analysis of the impact of migration on the EU 27's NUTS-2 regions in the period 2000-2007. While our results indicate that migration had no statistical impact on regional unemployment in the EU it had a significant impact on both per-capita GDP and productivity. The coefficients suggest that a 1 percent increase in immigration to immigration regions increased per-capita GDP by about 0.02 percent and productivity by about 0.03 percent. For emigration regions a 1 percent increase in the emigration rate leads to a reduction of 0.03 percent in per-capita GDP and 0.02 percent in productivity. Since immigration regions are also often regions with above-average GDP and productivity while emigration regions in Europe practically all have below-average GDP, migration seems to induce divergence rather than convergence.
Keywords: 330; Migration; Convergence; Unemployment; Internationale Migration; Wirkungsanalyse; Räumliche Verteilung; EU-Staaten